Preparation method of double-layer protective coating with self-repairing characteristic

By forming an in-situ oxidation/nitriding layer on the high-entropy alloy coating, the problem of insufficient bonding strength between the high-entropy alloy coating and the matrix is ​​solved, and the self-repair of the coating and better protection performance are achieved.

CN119553267AActive Publication Date: 2025-03-04HARBIN ENG UNIV
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411726738.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-03-04
Estimated Expiration
2044-11-28

AI Technical Summary

Technical Problem

The high entropy alloy coating has low bond strength with the substrate, making it difficult to maintain long-term service stability under harsh working environments.

Method used

The preparation method of a double-layer protective coating is adopted. The bottom layer is a high-entropy alloy coating, which is formed by a high-energy beam deposition process. The top layer is an in-situ oxidation/nitride layer. The self-oxidation/nitride characteristics of the easy-to-oxidation/nitride element are used to form a stable intermetallic compound and an oxidation/nitride layer.

Benefits of technology

It improves the corrosion resistance and high temperature resistance of the coating, enhances the bonding strength with the matrix, and realizes self-healing in an oxygen-rich/nitrogen environment, significantly improving the protection performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119553267A_ABST
    Figure CN119553267A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a double-layer protective coating with a self-repairing characteristic, and aims to solve the problems that the bonding strength of a high-entropy alloy coating and a matrix is relatively low, and the long-term service stability is difficult to maintain. The preparation method comprises the following steps: 1, substrate pretreatment; secondly, the average atomic radius difference, the VEC, the mixed entropy and the mixed enthalpy of the high-entropy alloy multi-element system are calculated, and corresponding elementary substance powder is mixed and subjected to ball milling treatment; 3, performing cladding deposition on the mixed metal powder by adopting a high-energy beam deposition process; fourthly, the high-entropy alloy coating is ground, polished and cleaned; and fifthly, an oxidation process or a nitriding process is adopted for forming an oxidation layer or a nitriding layer on the high-entropy alloy coating in situ. The double-layer protective coating with the self-repairing characteristic provided by the invention has double-layer protection of the high-entropy alloy coating with excellent corrosion resistance and the in-situ oxidation / nitridation layer, and the high-entropy alloy coating forms a stable intermetallic compound by utilizing dilution of a matrix in design, so that the matching property of the coating and the matrix is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of composite coatings, and in particular relates to a method for preparing a double-layer protective coating with self-repairing characteristics. Background Art

[0002] Surface technology has a wide range of applications in improving the surface performance of components. High entropy alloy coatings have broader application prospects than traditional protective coatings due to their four major effects. For example, mature AlCoCrFeNi eutectic high entropy coatings have been initially applied to tools such as cutting tools. The excellent corrosion resistance and other properties of high entropy alloy coatings have been applied in many fields and components, but in the application exploration, it was found that due to the difference in thermal properties between the coating and the substrate, there are problems such as peeling caused by poor coating formability, complex phases, and low bonding strength. It is difficult to maintain long-term service stability in increasingly harsh working environments. Therefore, it is urgent to optimize the long-term service performance of the coating through structural design while ensuring good bonding between the substrate and the high entropy alloy coating. Summary of the invention

[0003] The purpose of the present invention is to solve the problem that the bonding strength between the high entropy alloy coating and the substrate is low and it is difficult to maintain long-term service stability, and to propose a method for preparing a double-layer protective coating with self-repairing characteristics.

[0004] The preparation method of the double-layer protective coating with self-repairing characteristics of the present invention is achieved by the following steps:

[0005] 1. Grinding, polishing and cleaning the surface of the substrate in sequence to obtain a pretreated substrate;

[0006] 2. Analyze the metal elements in the matrix, select an element with a metal element content of not less than 30% or the element with the largest metal element content in the matrix as an added element, select 2 to 6 elements from the easily oxidized / nitrided elements as alloying elements, and use the added elements and the alloying elements to form a high entropy alloy multi-element system, and then calculate the average atomic radius difference δ, VEC (valence electron concentration), ΔSmix (mixing entropy) and ΔHmix (mixing enthalpy) of the high entropy alloy multi-element system (including matrix elements and easily oxidized / nitrided elements), so that the average atomic radius difference δ of the high entropy alloy multi-element system is ≤15%, 6.7 (e / a) ≤ VEC ≤ 8 (e / a), 12 J / (mol·K) ≤ ΔSmix ≤ 17.5 J / (mol·K) and -22 kJ / mol ≤ ΔHmix ≤ 7 kJ / mol;

[0007] The corresponding single substance powders of the additive element and the alloy element are put into a high-energy ball mill for ball milling to obtain a mixed powder;

[0008] 3. coating the mixed powder on the pretreated substrate surface, and performing melt cladding deposition on the mixed metal powder using a high energy beam deposition process to form a high entropy alloy coating;

[0009] 4. grinding, polishing and cleaning the high entropy alloy coating in sequence to obtain a substrate with the high entropy alloy coating;

[0010] 5. An oxidation process is used to form an oxide layer in situ on the high entropy alloy coating, or a nitridation process is used to form a nitride layer in situ, thereby obtaining a double-layer protective coating with self-repairing characteristics;

[0011] The easily oxidizable / nitridable elements in step 2 are Cr, Fe, Al, Si, Co, Ni, Zr and Ti;

[0012] The oxidation process in step five is a high temperature oxidation process or a micro-arc oxidation process, and the nitridation process is an ion nitridation or a carbonitriding process.

[0013] The bottom layer of the double-layer protective coating with self-repairing characteristics of the present invention is a high entropy alloy coating, and the surface layer is an in-situ oxidation / nitridation layer. The high entropy alloy coating has excellent corrosion resistance and high temperature resistance, the selected elements are all easily oxidized / nitrided elements, and the internal structure of the coating is an intermetallic compound; the in-situ oxidation / nitridation layer is formed by pre-oxidation / nitridation catalysis on the surface of the high entropy alloy coating.

[0014] The double-layer protective coating with self-repairing characteristics provided by the present invention has a double-layer protection of a high entropy alloy coating with excellent corrosion resistance and an in-situ oxidation / nitridation layer, wherein the high entropy alloy coating is designed to utilize the dilution of the substrate to form a stable intermetallic compound, solving the problem of insufficient matching between the coating and the substrate. At the same time, due to the presence of the in-situ oxidation / nitridation layer, it belongs to a negative oxygen / nitrogen concentration gradient in an oxygen-rich environment, has stronger stability, and due to the self-oxidation / nitridation characteristics of the selected elements of the high entropy alloy, it can complete self-repair in an oxygen-rich / nitrogen environment, showing more excellent protective performance. The preparation method of the coating is reliable and efficient, and can ensure that the coating structure and size are stable and controllable.

[0015] The double-layer protective coating with self-repairing characteristics described in the present invention can be prepared on the surface of medium and high temperature components, such as nuclear power plant loop pipes, hot end components, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 Schematic diagram of the preparation process of the double-layer protective coating with self-repairing characteristics of the present invention;

[0017] Figure 2 TEM image of the phase structure of the high entropy alloy coating obtained in Example 1;

[0018] Figure 3A schematic diagram of the self-repairing process of the double-layer protective coating with self-repairing characteristics of the present invention;

[0019] Figure 4 Phase structure analysis diagram of the double-layer protective coating (high entropy alloy coating) with self-repairing characteristics prepared in Example 1, including (a) microstructure of ZrNbCrAlFe coating; (b) element distribution of ZrNbCrAlFe coating; (c) high-magnification microstructure of ZrNbCrAlFe coating; (d) phase structure of ZrNbCrAlFe coating;

[0020] Figure 5 A cross-sectional view of a double-layer protective coating with self-healing characteristics prepared in Example 1;

[0021] Figure 6 This is an element distribution diagram of the double-layer protective coating with self-repairing characteristics prepared in Example 1;

[0022] Figure 7 This is a phase structure analysis diagram of the double-layer protective coating with self-repairing characteristics prepared in Example 2;

[0023] Figure 8 A cross-sectional view of an in-situ oxide layer in a double-layer protective coating with self-repairing characteristics in Example 2;

[0024] Fig. 9 Element distribution diagram of the double-layer protective coating with self-repairing characteristics prepared in Example 2;

[0025] Fig.10 A cross-sectional view of an in-situ oxide layer in a double-layer protective coating with self-repairing characteristics prepared in Example 3;

[0026] Fig.11 This is the element distribution diagram of the double-layer protective coating with self-repairing characteristics prepared in Example 3;

[0027] Fig.12 Phase structure analysis diagram of the double-layer protective coating with self-repairing characteristics prepared in Example 4, (a-f) element distribution of the FeCoCrAlNi coating; (g) line scanning distribution diagram of each element of the FeCoCrAlNi coating; (h) TEM microstructure diagram of the FeCoCrAlNi coating; (i-j) FCC and BCC phase diffraction spots of the FeCoCrAlNi coating;

[0028] Fig.13 A cross-sectional view of the in-situ nitridation layer of the double-layer protective coating with self-repairing characteristics prepared in Example 4;

[0029] Fig.14 This is the element distribution diagram of the double-layer protective coating with self-healing characteristics prepared in Example 4. DETAILED DESCRIPTION

[0030] Specific implementation method 1: The preparation method of the double-layer protective coating with self-repairing characteristics in this implementation method is implemented according to the following steps:

[0031] 1. Grinding, polishing and cleaning the surface of the substrate in sequence to obtain a pretreated substrate;

[0032] 2. Analyze the metal elements in the matrix, select an element with a metal element content of not less than 30% or the element with the largest metal element content in the matrix as an added element, select 2 to 6 elements from the easily oxidized / nitrided elements as alloying elements, and use the added elements and the alloying elements to form a high entropy alloy multi-element system, and then calculate the average atomic radius difference δ, VEC (valence electron concentration), ΔSmix (mixing entropy) and ΔHmix (mixing enthalpy) of the high entropy alloy multi-element system (including matrix elements and easily oxidized / nitrided elements), so that the average atomic radius difference δ of the high entropy alloy multi-element system is ≤15%, 6.7 (e / a) ≤ VEC ≤ 8 (e / a), 12 J / (mol·K) ≤ ΔSmix ≤ 17.5 J / (mol·K) and -22 kJ / mol ≤ ΔHmix ≤ 7 kJ / mol;

[0033] The corresponding single substance powders of the additive element and the alloy element are put into a high-energy ball mill for ball milling to obtain a mixed powder;

[0034] 3. coating the mixed powder on the pretreated substrate surface, and performing melt cladding deposition on the mixed metal powder using a high energy beam deposition process to form a high entropy alloy coating;

[0035] 4. grinding, polishing and cleaning the high entropy alloy coating in sequence to obtain a substrate with the high entropy alloy coating;

[0036] 5. An oxidation process is used to form an oxide layer in situ on the high entropy alloy coating, or a nitridation process is used to form a nitride layer in situ, thereby obtaining a double-layer protective coating with self-repairing characteristics;

[0037] The easily oxidizable / nitridable elements in step 2 are Cr, Fe, Al, Si, Co, Ni, Zr and Ti;

[0038] The oxidation process in step five is a high temperature oxidation process or a micro-arc oxidation process, and the nitriding process is an ion nitriding or a carbonitriding process.

[0039] When calculating the average atomic radius difference δ, VEC (valence electron concentration), ΔSmix and ΔHmix of the high entropy alloy multi-component system in step 1 of this embodiment, the molar concentration range of the added element is selected to be between 15% and 35%.

[0040] In step 2 of this embodiment, a plurality of single substance powders are selected according to the molar concentration ratio of the additive elements and the alloying elements in the high entropy alloy multi-component system, and are placed in a high energy ball mill for ball milling.

[0041] In this embodiment, when there are more than three phase structures in the high entropy alloy coating in step three, step two selects 2 to 3 metal element powders from easily oxidized / nitrided metals; when there are less than three phase structures in the high entropy alloy coating in step three, step two selects 3 to 6 metal element powders from easily oxidized / nitrided metals to avoid the appearance of overly complex structures.

[0042] The present embodiment provides a method for preparing a double-layer protective coating with self-repairing characteristics, in which a high-entropy alloy coating is prepared on the surface of a substrate as a bottom layer using high-energy beam deposition technology. Since the elements selected for the high-entropy alloy coating are easily oxidized / nitrided, an in-situ oxidation / nitridation layer can be formed on the surface of the high-entropy alloy coating through pre-oxidation / nitridation catalysis. When the in-situ oxidation / nitridation layer is broken, the high-entropy alloy coating reacts with oxygen again to form an oxidation / nitridation layer, thereby achieving a self-repairing effect.

[0043] Specific implementation method 2: The difference between this implementation method and specific implementation method 1 is that the calculation formula of the average atomic radius difference δ of the high entropy alloy multi-element system in step 2 is as follows:

[0044]

[0045] Among them C i is the molar percentage of each element (i) in the high entropy alloy multi-element system, r i is the atomic radius, and r is the average atomic radius of all elements in the high entropy alloy multi-element system.

[0046] Specific implementation method three: This implementation method is different from specific implementation methods one or two in that the calculation formula of the VEC of the high entropy alloy multi-element system in step two is as follows:

[0047]

[0048] Among them C i is the molar percentage of each element (i) in the high entropy alloy multi-element system, (VEC) i is the valence electron concentration of each element (i) in the high entropy alloy multi-element system.

[0049] Specific embodiment 4: This embodiment is different from specific embodiments 1 to 3 in that the particle size of the mixed metal powder in step 2 is 45 to 80 μm.

[0050] The purpose of limiting the powder particle size within this range in this embodiment is to have closer sizes, which is conducive to the mutual solid solution of elements and the formation of a stable structure (including a single solid solution and an intermetallic compound).

[0051] Specific implementation method five: This implementation method is different from specific implementation methods one to four in that the laser power is controlled to be 1000-1500W in the high energy beam deposition process in step three.

[0052] This embodiment limits the deposition power, which can ensure a higher energy density and is conducive to the full combination of matrix elements and alloy elements.

[0053] Specific implementation method 6: The difference between this implementation method and any one of specific implementation methods 1 to 5 is that in step 3, the deposition rate in the high energy beam deposition process is controlled to be 10 to 15 mm / s.

[0054] This embodiment limits the deposition rate, which can ensure a higher energy density and is conducive to the full combination of matrix elements and alloy elements.

[0055] Specific embodiment 7: The difference between this embodiment and any one of specific embodiments 1 to 6 is that the thickness of the high entropy alloy coating in step 3 is 400-800 μm.

[0056] Specific implementation example eight: This implementation example is different from any one of specific implementation examples one to seven in that the thickness of the oxide layer or nitride layer in step five is 20 to 50 μm.

[0057] Specific embodiment nine: This embodiment differs from any one of specific embodiments one to eight in that the high temperature oxidation process is to place the substrate with the high entropy alloy coating into a high temperature furnace and perform high temperature oxidation treatment at a temperature of 600 to 800° C. in an air atmosphere or an oxygen atmosphere.

[0058] Specific embodiment ten: The difference between this embodiment and any one of specific embodiments one to nine is that the ion nitriding process is to apply a voltage of 800V between the substrate with the high entropy alloy coating and the furnace body of the vacuum furnace, using pure ammonia as the gas source, and nitriding for 5 to 6 hours at a nitriding temperature of 520°C and a gas pressure of 350Pa.

[0059] Embodiment 1: The preparation method of the double-layer protective coating with self-repairing characteristics in this embodiment is implemented according to the following steps:

[0060] 1. Grinding, polishing and cleaning the surface of the zirconium alloy substrate in sequence to obtain a pretreated substrate;

[0061] 2. The main metal element component of the analysis matrix is ​​Zr. Four single powders of Nb, Fe, Cr and Al are selected from the easily oxidized / nitrided elements as alloying elements. The element Zr and the alloying elements Nb, Fe, Cr and Al are added to form a high entropy alloy multi-element system. The atomic radius difference δ, VEC (valence electron concentration), ΔSmix (mixing entropy) and ΔHmix (mixing enthalpy) of the high entropy alloy multi-element system are calculated to make the average atomic radius difference δ of the high entropy alloy multi-element system ≤15%, 6.7 (e / a) ≤VEC ≤8 (e / a), 12 J / (mol·K) ≤ΔSmix ≤17.5 J / (mol·K) and -22 kJ / mol ≤ΔHmix ≤7 kJ / mol;

[0062] The calculation formula of atomic radius difference δ is as follows:

[0063]

[0064] Among them C i is the molar percentage of each element (i) in the high entropy alloy multi-element system, r i is the atomic radius, r is the average atomic radius of all elements in the high entropy alloy multi-element system;

[0065] The calculation formula of ΔHmix (mixing enthalpy) is as follows:

[0066]

[0067] Where ΔH mix is the enthalpy of mixing, Ω ij is the mixing enthalpy of the alloy (between two elements), C i and C j is the molar percentage of different elements;

[0068] ΔS mix The calculation formula is as follows:

[0069]

[0070] Where ΔS mix is the mixing entropy, R is the gas constant, C i is the molar percentage of each element (i) in the high entropy alloy multi-component system;

[0071] The calculation formula of VEC (valence electron concentration) is as follows:

[0072]

[0073] Among them C i is the molar percentage of each element (i) in the high entropy alloy multi-element system, (VEC) iis the valence electron concentration of each element (i) in the high entropy alloy multi-element system;

[0074] The relevant calculation results of the high entropy alloy multi-element system in this embodiment are: the average atomic radius difference is 9.02%, VEC = 6.71e / a, ΔSmix = 13.92mol / K, ΔHmix = -17.64mol / K, which meets the requirements;

[0075] Putting Zr, Nb, Fe, Cr and Al metal single substance powders into a high energy ball mill for ball milling according to the molar ratio of Zr, Nb, Fe, Cr and Al being 10:8:50:16:16 to obtain a mixed metal powder with a particle size of 80 to 100 μm;

[0076] 3. Coating the mixed metal powder on the pretreated substrate surface, using a high-energy beam deposition process to perform cladding deposition on the mixed metal powder, controlling the laser power to 1200W and the deposition rate to 10mm / s, to form a high-entropy alloy coating;

[0077] 4. grinding, polishing and cleaning the high entropy alloy coating in sequence to obtain a substrate with the high entropy alloy coating;

[0078] 5. The substrate with the high-entropy alloy coating is placed in a high-temperature furnace and treated at 600°C for 80 hours in an air atmosphere to form an oxide layer in situ on the high-entropy alloy coating. When the temperature of the high-temperature furnace drops to room temperature, a double-layer protective coating with self-healing characteristics is obtained.

[0079] The double-layer protective coating with self-repairing characteristics obtained in this embodiment has a bottom layer of ZrNbCrAlFe high entropy alloy coating, in which Zr and Nb elements are elements in the zirconium alloy matrix, the coating thickness is 800μm, and an intermetallic compound Zr(Fe,Cr)2 is formed, the bonding strength is 95Mpa, the thickness of the in-situ oxide layer is 35-45μm, and the phase structure analysis diagram of the high entropy alloy coating is as follows: Figure 4 As shown, the cross-section of the in-situ oxide layer is shown in Figure 5 As shown, the element distribution diagram of the double-layer protective coating is as follows Figure 6 As shown. Combined Figure 4-Figure 6 It can be seen that a double-layer protective coating with a bottom layer of ZrNbCrAlFe and a surface layer of an in-situ oxide layer was prepared.

[0080] Embodiment 2: The preparation method of the double-layer protective coating with self-repairing characteristics in this embodiment is implemented according to the following steps:

[0081] 1. Grinding, polishing and cleaning the surface of the zirconium alloy in sequence to obtain a pretreated substrate;

[0082] 2. The main metal element component of the analysis matrix is ​​Zr. Four single powders of Nb, Cr, Si and Al are selected from the easily oxidized / nitrided elements as alloying elements to add the element Zr and the alloying elements Nb, Si, Cr and Al to form a high entropy alloy multi-element system. The atomic radius difference, VEC (valence electron concentration), ΔSmix (mixing entropy) and ΔHmix (mixing enthalpy) of the high entropy alloy multi-element system are calculated to make the average atomic radius difference δ≤15%, 6.7(e / a)≤VEC≤8(e / a), 12J / (mol·K)≤ΔSmix≤17.5J / (mol·K) and -22kJ / mol≤ΔHmix≤7kJ / mol;

[0083] The atomic radius difference, VEC (valence electron concentration), ΔSmix (mixing entropy) and ΔHmix (mixing enthalpy) of the high entropy alloy multi-element system are calculated according to the following formula:

[0084]

[0085]

[0086] The relevant calculation results of the high entropy alloy multi-element system in this embodiment are: the average atomic radius difference is 10.12%, VEC = 7.01e / a, ΔSmix = 12.77mol / K, ΔHmix = -14.34mol / K, which meets the requirements;

[0087] The Zr, Nb, Cr, Al and Si single substance powders are placed in a high energy ball mill for ball milling according to a molar ratio of Zr, Nb, Cr, Al and Si of 20:8:25:33:14 to obtain a mixed metal powder with a particle size of 80 to 100 μm;

[0088] 3. Coating the mixed powder on the pretreated substrate surface, using a high-energy beam deposition process to melt-clad the mixed metal powder, controlling the laser power to 1000W and the deposition rate to 15mm / s to form a high-entropy alloy coating;

[0089] 4. grinding, polishing and cleaning the high entropy alloy coating in sequence to obtain a substrate with the high entropy alloy coating;

[0090] 5. The substrate with the high-entropy alloy coating is placed in a high-temperature furnace and treated at 650°C for 20 hours in an air atmosphere to form an oxide layer in situ on the high-entropy alloy coating. When the temperature of the high-temperature furnace drops to room temperature, a double-layer protective coating with self-healing characteristics is obtained.

[0091] The double-layer protective coating with self-repairing characteristics obtained in this embodiment has a bottom layer of ZrNbCrAlSi high entropy alloy coating with a coating thickness of 750μm, forming two intermetallic compounds, namely Zr(Ai,Si) and Zr2Cr, with a bonding strength of 98Mpa and an in-situ oxide layer thickness of 35-45μm. The phase structure analysis of the high entropy alloy coating is shown in Figure 2. Figure 7 As shown, the in-situ oxidation cross-section diagram is as follows Figure 8 As shown, the element distribution diagram of the double-layer protective coating is as follows Fig. 9 As shown, combined Figure 7-Figure 9 It can be seen that a double-layer protective coating with a bottom layer of ZrNbCrAlSi and a surface layer of an in-situ oxide layer was prepared.

[0092] Embodiment 3: The preparation method of the double-layer protective coating with self-repairing characteristics in this embodiment is implemented according to the following steps:

[0093] 1. Grinding, polishing and cleaning the surface of the zirconium alloy in sequence to obtain a pretreated substrate;

[0094] 2. The main metal component of the analysis matrix is ​​Zr. Four single powders of Nb, Cr, Si and Al are selected from the easily oxidized / nitrided elements as alloying elements to add the element Zr and the alloying elements Nb, Cr, Si and Al to form a high entropy alloy multi-element system. The atomic radius difference, VEC (valence electron concentration), ΔSmix (mixing entropy) and ΔHmix (mixing enthalpy) of the high entropy alloy multi-element system are calculated to make the average atomic radius difference δ≤15%, 6.7(e / a)≤VEC≤8(e / a), 12J / (mol·K)≤ΔSmix≤17.5J / (mol·K) and -22kJ / mol≤ΔHmix≤7kJ / mol;

[0095] The calculation is done according to the following formula:

[0096]

[0097]

[0098] The relevant calculation results of the high entropy alloy multi-element system in this embodiment are: the average atomic radius difference is 14.12%, VEC = 7.82e / a, ΔSmix = 14.97mol / K, ΔHmix = -20.09mol / K, which meets the requirements;

[0099] The Zr, Nb, Cr, Al and Si single substance powders are placed in a high energy ball mill for ball milling according to a molar ratio of Zr, Nb, Cr, Al and Si of 20:8:25:33:14 to obtain a mixed metal powder with a particle size of 60 to 100 μm;

[0100] 3. Coating the mixed powder on the pretreated substrate surface, using a high-energy beam deposition process to melt-clad the mixed metal powder, controlling the laser power to 1000W and the deposition rate to 15mm / s to form a high-entropy alloy coating;

[0101] 4. grinding, polishing and cleaning the high entropy alloy coating in sequence to obtain a substrate with the high entropy alloy coating;

[0102] 5. Place the substrate with high entropy alloy coating in an electrolyte, use a micro-arc oxidation process, adopt a pulse power supply, the electrolyte is a mixed solution of 20g / L Na2O·nSiO2, 8g / LKF and 2g / LNaOH, the pulse frequency is 700Hz, the duty cycle is 20%, and the forward voltage is controlled to be 100V and the negative voltage is 10V within 1-5min; the forward voltage is 150V and the negative voltage is 10V from 5 to 13min; the forward voltage is 350V and the negative voltage is 10V from 13 to 15min; the forward voltage is 350V and the negative voltage is 10V from 15 to 20min; the oxidation time is a total of 20min, an oxide layer is formed in situ on the high entropy alloy coating, and the temperature of the high-temperature furnace is reduced to room temperature to obtain a double-layer protective coating with self-healing characteristics.

[0103] The double-layer protective coating with self-repairing characteristics obtained in this embodiment has a bottom layer of ZrNbCrAlSi high entropy alloy coating with a coating thickness of 750μm, forming two intermetallic compounds, namely Zr(Ai,Si) and Zr2Cr, with a bonding strength of 98Mpa and an in-situ oxide layer thickness of 1-2μm. The phase structure of the high entropy alloy coating is the same as Figure 7 The in-situ oxidation cross-section diagram is as follows Fig.10 As shown, the element distribution diagram of the double-layer protective coating is as follows Fig.11 As shown, combined Figure 7-Figure 11 It can be seen that a double-layer protective coating with a bottom layer of ZrNbCrAlSi and a surface layer of an in-situ oxidation layer was prepared.

[0104] Embodiment 4: The preparation method of the double-layer protective coating with self-repairing characteristics in this embodiment is implemented according to the following steps:

[0105] 1. Grinding, polishing and cleaning the surface of 20Cr stainless steel in sequence to obtain a pretreated substrate;

[0106] 2. The main metal component of the analysis matrix is ​​Fe. Four single powders of Co, Cr, Al and Ni are selected from the easily oxidized / nitrided elements as alloying elements to add element Fe and alloying elements Co, Cr, Al and Ni to form a high entropy alloy multi-element system. The atomic radius difference, VEC (valence electron concentration), ΔSmix (mixing entropy) and ΔHmix (mixing enthalpy) of the high entropy alloy multi-element system are calculated to make the average atomic radius difference δ≤15%, 6.7(e / a)≤VEC≤8(e / a), 12J / (mol·K)≤ΔSmix≤17.5J / (mol·K) and -22kJ / mol≤ΔHmix≤7kJ / mol;

[0107] The calculation is done according to the following formula:

[0108]

[0109]

[0110] The relevant calculation results of the high entropy alloy multi-element system in this embodiment are: the average atomic radius difference is 8.12%, VEC = 6.94e / a, ΔSmix = 13.97mol / K, ΔHmix = -7.31mol / K, which meets the requirements;

[0111] Fe, Co, Cr, Al and Ni metal powders are placed in a high-energy ball mill for ball milling according to a molar ratio of Fe, Co, Cr, Al and Ni of 1:1:1:1:1 to obtain a mixed metal powder with a particle size of 60 to 80 μm;

[0112] 3. Coating the mixed metal powder on the pretreated substrate surface, using a high-energy beam deposition process to perform cladding deposition on the mixed metal powder, controlling the laser power to 1000W and the deposition rate to 15mm / s, to form a high-entropy alloy coating;

[0113] 4. grinding, polishing and cleaning the high entropy alloy coating in sequence to obtain a substrate with the high entropy alloy coating;

[0114] 5. An in-situ nitrided layer is prepared on the surface of the high entropy alloy coating using an ion nitriding process. The vacuum degree is 0.8 Pa, the nitriding temperature is 520°C, the nitriding time is 6 h, the gas pressure is 350 Pa, the voltage is 800 V, the DC power supply is 10 A, and the AC power supply is 25 A, thereby obtaining a double-layer protective coating with self-healing characteristics.

[0115] The double-layer protective coating with self-repairing characteristics obtained in this embodiment has a bottom layer of FeCoCrAlNi high entropy alloy coating, a coating thickness of 1800μm, forming two phase structures, namely FCC phase and BCC phase, a bonding strength of 98Mpa, and an in-situ oxide layer thickness of 3μm. The phase structure of the high entropy alloy coating is shown in Fig.12 As shown, the in-situ oxidation cross-section diagram is as follows Fig.13 As shown, the element distribution diagram of the double-layer protective coating is as follows Fig.14 As shown, combined Figure 12-14 It can be seen that a double-layer protective coating with a bottom layer of FeCoCrAlNi and a surface layer of in-situ nitrided layer was prepared.

Claims

1. A method for preparing a double-layer protective coating with self-repairing characteristics, characterized in that The preparation method of the double-layer protective coating with self-repairing characteristics is achieved by the following steps:

1. Grinding, polishing and cleaning the surface of the substrate in sequence to obtain a pretreated substrate; 2. Analyze the metal elements in the matrix, select an element with a metal element content of not less than 30% or the element with the largest metal element content in the matrix as an added element, select 2 to 6 elements from the easily oxidizable / nitridable elements as alloying elements, and use the added elements and the alloying elements to form a high entropy alloy multi-element system, and then calculate the average atomic radius difference δ, VEC, ΔSmix and ΔHmix of the high entropy alloy multi-element system, so that the average atomic radius difference δ of the high entropy alloy multi-element system is ≤15%, 6.7(e / a)≤VEC≤8(e / a), 12J / (mol·K)≤ΔSmix≤17.5J / (mol·K) and -22kJ / mol≤ΔHmix≤7kJ / mol; The corresponding single substance powders of the additive element and the alloy element are put into a high-energy ball mill for ball milling to obtain a mixed powder; 3. coating the mixed powder on the pretreated substrate surface, and performing melt cladding deposition on the mixed metal powder using a high energy beam deposition process to form a high entropy alloy coating; 4. grinding, polishing and cleaning the high entropy alloy coating in sequence to obtain a substrate with the high entropy alloy coating; 5. An oxidation process is used to form an oxide layer in situ on the high entropy alloy coating, or a nitridation process is used to form a nitride layer in situ, thereby obtaining a double-layer protective coating with self-repairing characteristics; The easily oxidizable / nitridable elements in step 2 are Cr, Fe, Al, Si, Co, Ni, Zr and Ti; The oxidation process in step five is a high temperature oxidation process or a micro-arc oxidation process, and the nitridation process is an ion nitridation process or a carbonitriding process.

2. The method for preparing a double-layer protective coating with self-repairing characteristics according to claim 1, characterized in that The calculation formula for the average atomic radius difference δ of the high entropy alloy multi-element system in step 2 is as follows: Among them C i is the molar percentage of each element in the high entropy alloy multi-element system, r i is the atomic radius, and r is the average atomic radius of all elements in the high entropy alloy multi-element system.

3. The method for preparing a double-layer protective coating with self-repairing characteristics according to claim 1, characterized in that The calculation formula of VEC of high entropy alloy multi-element system in step 2 is as follows: Among them C i is the molar percentage of each element in the high entropy alloy multi-element system, (VEC) i is the valence electron concentration of each element in the high entropy alloy multi-element system.

4. The method for preparing a double-layer protective coating with self-repairing characteristics according to claim 1, characterized in that The particle size of the mixed metal powder in step 2 is 45 to 80 μm.

5. The method for preparing a double-layer protective coating with self-repairing characteristics according to claim 1, characterized in that In step 3, the laser power is controlled to be 1000-1500W in the high energy beam deposition process.

6. The method for preparing a double-layer protective coating with self-repairing characteristics according to claim 1, characterized in that In step 3, the deposition rate in the high energy beam deposition process is controlled to be 10-15 mm / s.

7. The method for preparing a double-layer protective coating with self-repairing characteristics according to claim 1, characterized in that In step three, the thickness of the high entropy alloy coating is 400-800 μm.

8. The method for preparing a double-layer protective coating with self-repairing characteristics according to claim 1, characterized in that In step five, the thickness of the oxide layer or the nitride layer is 20 to 50 μm.

9. The method for preparing a double-layer protective coating with self-repairing characteristics according to claim 1, characterized in that The high temperature oxidation process is to place the substrate with the high entropy alloy coating into a high temperature furnace and perform high temperature oxidation treatment at a temperature of 600 to 800° C. in an air atmosphere or an oxygen atmosphere.

10. The method for preparing a double-layer protective coating with self-repairing characteristics according to claim 1, characterized in that The ion nitriding process is to apply a voltage of 800V between the substrate with the high entropy alloy coating and the furnace body of the vacuum furnace, use pure ammonia as the gas source, and nitridate for 5 to 6 hours at a nitriding temperature of 520°C and a gas pressure of 350Pa.

Citation Information

Patent Citations

  • HIGH-ENTROPY ALLOY MATERIAL AND METHOD FOR PRODUCING A COATING BY USE OF THESE

    BE1030353A1

  • High-entropy coating for surface of iron substrate and preparation method of high-entropy coating

    CN105862036A

  • High entropy alloy coating as well as preparation method and application thereof

    CN107299342A

  • Laser-cladding high-hardness high-wear-resistance high-entropy alloy coating and preparation method thereof

    CN115928066A

  • Method for preparing in-situ synthesized nano precipitated phase reinforced high-entropy alloy coating through plasma spraying

    CN116411235A